ANALISIS FAKTOR EKSTERNAL DAN INTERNAL TERHADAP PENYALURAN KREDIT PERBANKAN DI INDONESIA (Studi Kasus Bank Umum) - Cahyaning P, Wanda Annisa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The existence of credit as a source of capital has a close relationship with economic growth. Unfortunately, the credit growth of recent years continue to weaken. The weakening of credit growth is influenced by factors of banking own and factors beyond the control of banking, namely macroeconomic conditions. This study raised about how much influence of external factors and internal factors of the Commercial Bank lending as banks that manage more than 90% Third Party Funds across Indonesia. External factors used were BI rate, exchange rate and economic growth. While the internal factors that Net-performing loans (NPLs) and Third Party Fund (TPF). This study used a multiple regression analysis with the data period from January 2009 to June 2014. Based on the research results that external factors, BI Rate has a significant negative effect on commercial bank lending, exchange rate and economic growth have a significant positive effect on commercial bank lending. While the internal factors, Net-performing loans (NPLs) has no significant positive effect on commercial bank lending. While Third Party Fund (TPF) has positive and significant impact on commercial bank lending. Kata kunci: Kredit, Bank Umum, BI Rate, Kurs, Pertumbuhan ekonomi, NPL.